Effect of Voltage and Gap on Micro-Nickel-Column Growth Patterns in Localized Electrochemical Deposition. Issue 6 (31st March 2017) - Wang, Fuliang; Sun, Jiadong; Liu, Defu; Wang, Yan; Zhu, Wenhui
Abstract : Localized electrochemical deposition (LECD) is an efficient and economical micro-manufacturing technology. Currently, nickel deposition with LECD is mainly used in cases of low voltages and small microanode–cathode gaps to avoid poor-quality micro-columns, but the deposition rate is low. To overcome this disadvantage, nickel deposition under different voltages and gaps is explored in this study, in order to simultaneously improve deposition rate and quality. Three growth patterns are proposed: the layer-by-layer deposition pattern under low-voltage/small-gap conditions (3.6 V/20 μm), which has deposition velocities as low as 0.19 μm/s, but the deposition has a smooth surface; the round-by-round growth pattern under high-voltage/small-gap conditions (4.6 V/20 μm), which has deposition velocities as high as 5.46 μm/s, but often results in rough columns with nodular structures; and the integration of the layer-by-layer and round-by-round methods under high-voltage/large-gap conditions (4.6 V/80 μm), which achieves a balance between relatively good surface quality and fast deposition (0.68 μm/s). Interestingly, the growth pattern was found to switch in gaps of less than 35 μm.